MET tyrosine kinase receptor expression and amplification as prognostic biomarkers of survival in gastroesophageal adenocarcinoma. Issue 6 (7th December 2016) - Catenacci, Daniel V. T.; Ang, Agnes; Liao, Wei‐Li; Shen, Jing; O'Day, Emily; Loberg, Robert D.; Cecchi, Fabiola; Hembrough, Todd; Ruzzo, Annamaria; Graziano, Francesco
Abstract : BACKGROUND: MET gene amplification and Met protein overexpression may be associated with a poor prognosis. The MET /Met status is typically determined with fluorescence in situ hybridization (FISH) and immunohistochemistry (IHC), respectively. Targeted proteomics uses mass spectrometry–based selected reaction monitoring (SRM) to accurately quantitate Met expression. FISH, IHC, and SRM analyses were compared to characterize the prognostic value of MET /Met in gastroesophageal adenocarcinoma (GEC). METHODS: Samples from 447 GEC patients were analyzed for MET gene amplification (FISH) and Met protein expression (IHC and SRM). Cox proportional hazards models and Kaplan‐Meier estimates were applied to explore relations between Met, overall survival (OS), and clinical/pathological characteristics. Spearman's rank coefficient was used to assess the correlation between parameters. RESULTS: Patients with MET ‐amplified tumors had worse OS when: the MET /centromere enumeration probe for chromosome 7 FISH ratio was ≥ 2 (hazard ratio [HR], 3.13; 95% confidence interval [CI], 1.84‐5.33), the MET gene copy number was ≥5 (HR, 2.51; 95% CI, 1.45‐4.34), or ≥ 10% of the cells had ≥15 copies (HR, 4.28; 95% CI, 2.18‐8.39). Similar observations were made with Met protein overexpression by IHC (≥1 + intensity in ≥ 25% of the tumor cell membrane: HR, 1.39; 95% CI, 1.04‐1.86) or SRM (≥400 amol/μg: HR, 1.76; 95% CI, 1.06‐2.90). A significant correlation was observed between MET FISH/Met IHC, MET FISH/Met SRM, and Met IHC/Met SRM; only MET FISH and Met SRM were independent negative prognostic biomarkers in multivariate analyses. CONCLUSIONS: MET amplification and overexpression, assessed by multiple methods, were associated with a worse prognosis in univariate analyses. However, only MET amplification by FISH and Met expression by SRM were independent prognostic biomarkers. Compared with IHC, SRM may provide an added benefit for informed decisions about Met‐targeted therapy. Cancer 2017;123:1061–70. © 2016 American Cancer Society . Abstract : In a large study, MET gene amplification, Met protein overexpression, or both, as assessed by various assays, are associated with a poor prognosis in univariate analyses. However, only MET amplification by fluorescence in situ hybridization and Met expression by selected reaction monitoring mass spectrometry are independent prognostic biomarkers; compared with immunohistochemistry, selected reaction monitoring may provide an added benefit for informed decisions about Met‐targeted therapy.